Talus Fracture in a 24-Year-Old Patient: A Case Report - I Gde Made Satya Wangsa; Wiradiputra, Agus Eka; Putra , Gusti Ngurah Paramartha Wijaya; Deker, Made (Jour Med Resh and Health Sci, 2022)
ABSTRACT Talus fracture is a type of fracture with a rare prevalence. We report a case of a fracture of the talus of the neck (Hawkins II) that occurred in a male patient aged 24 years. We report the results of the physical examination, therapy, radiological findings, follow-up, and clinical outcomes of the patient. Keywords: Talus fracture, radiology, follow up, clinical outcome